1995
DOI: 10.1038/hdy.1995.37
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme variability of brown trout (Salmo trutta L.) populations across the Rhenanian–Danubian watershed in southwest Germany

Abstract: Using horizontal agarose thin layer gel electrophoresis, 35 allozyme loci were screened in 233 brown trout (Salmo trutta L.) from 11 populations in southwest Germany across the RhenanianDanubian watershed. Polymorphism was found at 10 loci, with stocked populations exhibiting significantly increased polymorphism compared with unmanaged stocks (P= 0.2 19 vs. P= 0.132). Standard genetic distances between populations from different brooks averaged at D =0.01. Of the total gene diversity of GST =0.198, only a negl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 24 publications
(29 reference statements)
3
46
0
Order By: Relevance
“…3, phenotypes b). Similar variation has previously been described in populations from Greece by Karakousis & Trian- However, although side-by-side gel comparison was not made, our sMDHB1,2*75, MEP3*90 and SOD-i *120 alleles seem to be equivalent to the previous rare alleles MDH3*80 (Martinez et al, 1993), ME4*75 (Krieg & Guyomard, 1985) and SOD2*i35 (Riffel et al, 1995).…”
Section: Interpreting Ldha2* Variationsupporting
confidence: 49%
“…3, phenotypes b). Similar variation has previously been described in populations from Greece by Karakousis & Trian- However, although side-by-side gel comparison was not made, our sMDHB1,2*75, MEP3*90 and SOD-i *120 alleles seem to be equivalent to the previous rare alleles MDH3*80 (Martinez et al, 1993), ME4*75 (Krieg & Guyomard, 1985) and SOD2*i35 (Riffel et al, 1995).…”
Section: Interpreting Ldha2* Variationsupporting
confidence: 49%
“…The above observations can be augmented by considering similar studies of Danish (Hansen et al, 1993), German (Riffel et al, 1995) and Swiss (Largiardèr & Scholl, 1995, 1996 populations that have been excluded so far because of more than a century of hatchery stocking and translocations involving exogenous fish. As summarized in Table 4, the allelic distributions in these 48 additional locations are typical of those from unstocked areas selected for this study, but with evidence of varying degrees of interbreeding with hatchery populations of German (presumably Rhenish) origin (García-Marín et al, 1991).…”
Section: Additional Studiesmentioning
confidence: 99%
“…Entries in parentheses for maximum and minimum allele frequencies identify the number of samples where the value occurs. Danish data from Hansen et al (1993); German data from Riffel et al (1995); Swiss data from Largiadèr & Scholl (1995, 1996 contribution to the colonization of northern deglaciated areas.…”
Section: Glacial Refugiamentioning
confidence: 99%
“…The range of interpopulation genetic variability reported for European brown trout populations was 36-56% (Krieg and Guyomard 1985;Garcia-Marin et al 1991;Bernatchez and Osinov 1995;Riffel et al 1995;Apostolidis et al 2008). In this study, microsatellite data analyses of Turkish brown trout populations showed a range of interpopulation diversification of 22.88-45.78%.…”
Section: Genetic Differences and Phylogeographic Relationships Among mentioning
confidence: 78%
“…Therefore, it is preferable to use mtDNA and nuclear markers together for phylogenetic and population genetic studies. Allozymes were used for this aim, but they have not always been useful in discriminating between closely related populations (Riffel et al 1995;Estoup et al 1998;O'Connell and Wright 1997). Microsatellite DNA or simple sequence repeats (SSRs) exist at a high frequency in the nuclear genome of eukaryotes and are highly polymorphic codominant markers inherited in a Mendelian fashion (Tautz 1989).…”
mentioning
confidence: 99%